2020
DOI: 10.3390/genes11060691
|View full text |Cite
|
Sign up to set email alerts
|

From Genes to -Omics: The Evolving Molecular Landscape of Malignant Peripheral Nerve Sheath Tumor

Abstract: Malignant peripheral nerve sheath tumors (MPNST) are rare, aggressive soft tissue sarcomas that occur with significantly increased incidence in people with the neuro-genetic syndrome neurofibromatosis type I (NF1). These complex karyotype sarcomas are often difficult to resect completely due to the involvement of neurovascular bundles, and are relatively chemotherapy- and radiation-insensitive. The lifetime risk of developing MPNST in the NF1 population has led to great efforts to characterize the genetic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 96 publications
0
31
0
Order By: Relevance
“…In human medicine, the correlations between atypical neurofibromas and specific prognostic considerations and therapeutic options are still a matter of debate [ 50 , 57 ]. On the other hand, several studies in both the clinical field [ 72 , 73 , 74 ] and animal models [ 75 ] have recently reported that human atypical neurofibromas represent pre-malignant lesions that are able to progress to malignant PNSTs in a variable percentage of cases. In this context, the idea that atypical neurofibroma might represent a low-grade or a pre-malignant PNST variant rather than a frankly malignant PNST (also in goldfish) is supported by the apparent lack of correlation between death and gross evidence of tumor recurrence in the investigated animals, although a complete necropsy was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…In human medicine, the correlations between atypical neurofibromas and specific prognostic considerations and therapeutic options are still a matter of debate [ 50 , 57 ]. On the other hand, several studies in both the clinical field [ 72 , 73 , 74 ] and animal models [ 75 ] have recently reported that human atypical neurofibromas represent pre-malignant lesions that are able to progress to malignant PNSTs in a variable percentage of cases. In this context, the idea that atypical neurofibroma might represent a low-grade or a pre-malignant PNST variant rather than a frankly malignant PNST (also in goldfish) is supported by the apparent lack of correlation between death and gross evidence of tumor recurrence in the investigated animals, although a complete necropsy was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, the authors review the initial findings of NF1 as the gene responsible for neurofibromatosis type 1, its function as a RAS-GTPase-activating protein (RAS-GAP), and the spectrum of alterations in NF1 found in human disease. They then further summarize 16 additional genomic studies, covering 10 other recurrently altered genes, including BRAF, MET, EGFR, TYK2, ATRX and others [ 9 ]. Williams and Largaespada review the range of published MPNST model systems, including genetically-engineered mouse models (GEMM), the genes involved, and the limitations of these models.…”
mentioning
confidence: 99%
“…Previous studies have indicated that mutations affecting NF1, TP53, CDKN2A, PTEN and genes encoding components of PRC2 are the most common mutations that occur in MPNSTs regardless of whether they are www.nature.com/scientificreports/ NF1-associated, radiation-induced or sporadic [62][63][64][65][66] . Although NF1 and genes encoding PRC2 components are intact in 2XSB cells, these cells did have mutations in TP53, CDKN2A and PTEN, three genes which have been previously found to be mutated in both NF1-associated and sporadic MPNSTs 1,[67][68][69][70] . The TP53 (c.532C > G, exon 5, H178D; LOH) mutation [previously found in breast, genital tract, ovary, endometrial and lung cancers (COSMIC)] and homozygous CDKN2A loss that we identified in 2XSB cells promote genomic instability and loss of cell cycle checkpoints in other cancer types.…”
Section: Discussionmentioning
confidence: 79%